Default of treatment in patients with tuberculosis during 10 years after standardized drug treatment. (March 2015) - Jabbehdari, Sayena; Farnia, Parissa; Tabarsi, Payam; Hasani, Masoud; Velayati, Ali Akbar
Abstract: Background: Scaling-up in treatment for Mycobacterium tuberculosis (MTB) is a health priority. Currently, treatment regimens are long with complications, and default rates are very high. Tuberculosis (TB) patients who do not complete treatment pose a potential public health risk and are categorized as default to follow-up (DFU). Methods: In 2014, an anti-TB drug-resistance survey in Tehran, Iran, enrolled 1718 new and re-treatment patients who were TB, MDR-TB (multidrug-resistant) and old TB. TB was detected in these patients with positive acid fast bacilli (AFB) in smear and culture of sputum. Results: All patients received treatment with standardized first-line or second-line regimens (based on the type of TB infection). Patients are followed from the time of registration and treatment until the completion of treatment. This study reports the treatment outcomes of the retrospective study which was assessed from 2004 up to 2014. The reported cure rate for TB patients was 97.5% among new and old cases; 85.9% of patients ( n  = 1476) had no relapse; 13.7% of them ( n  = 236) had two or less than two relapses, and only 6 cases (0.4%) had more than two relapses; 10.5% of patients ( n  = 183) defaulted from anti-TB treatment and have not come back for follow-up after 52 weeks. Conclusions: These results showed the achievement of the National Tuberculosis Control Program implementation. It can be concluded that the treatment plans and appropriate follow-up of therapy have the greatest success in improving TB treatment outcomes.